A new approach to the solution of the optimal power flow problem based on the modified Newton's method associated to an augmented Lagrangian function - da Costa, GRM; Langona, K.; Alves, D. A. (Institute of Electrical and Electronics Engineers (IEEE), 1998)
This paper presents a new algorithm for optimal power flow problem. The algorithm is based on Newton's method which it works with an Augmented Lagrangian function associated with the original problem. The function aggregates all the equality and inequality constraints and is solved using the modified-Newton method. The test results have shown the effectiveness of the approach using the IEEE 30 and 638 bus systems.
Keywords: optimal power flow; Newton approach; optimization